Female Education and Contraceptives Use in Nigeria - Saheed O. Olayiwola; Bayo L.O. Kazeem; Fuein, Vera Kum (European Scientific Journal, ESJ, 2021)
Contraceptive use is considered important for protecting women’s health and rights, influencing fertility and population growth. This study examined the impact of female education on the use of contraceptives and fertility rate in Nigeria using 2013 and 2018 cohorts of Demography and Health Survey Data. The survey covers women ages 15 to 49 years. The study shows that women’s education, income level, and cultural value are important in explaining women’s reproductive behaviour. The results reveal that female education has a positive significant effect on contraceptives use and a significant negative effect on fertility rate. The contraceptives use and fertility models show that the effects become stronger with an increase in the level of education. Notably, the study shows no significant difference in the behavioural pattern of the factors that influenced contraceptive use and fertility rate in the 2013 and 2018 cohorts of demography and health survey data. The study concludes that female education is vital in encouraging the use of contraceptives and controlling the fertility rate. Hence, the government should invest more in women education to increase women's use of contraceptives, control fertility, and population growth, protect women's health and stimulate sustainable economic development.